Pengembangan Lembar Kerja Peserta Didik (LKPD) Berorientasi Problem Solving untuk Melatihkan Keterampilan Berpikir Kritis Peserta Didik pada Materi Asam Basa - Annisa Nabila; Utiya Azizah (Jurnal Penelitian Pendidikan IPA, 2024)
The purpose of this research was to describe the viability of using problem solving worksheets to teach students how to think critically about acid-base material. In assessing the viability of the student worksheets that have been developed, there are three factors that are taken into consideration, namely validity, practicality, and efficacy. In this study, 22 students from class XI MIPA 13 SMAN 1 Sidoarjo participated in a limited trial stage of the Research and Development (R&D) technique from Borg and Gall. The findings of this research indicate that validity, which comprises construct and content validity, each received a mode value of four using appropriate standards. Based on student reaction surveys, practicality reached 92.80% with extremely practical standards, and relevant student activities in the first and second meetings respectively obtained a percentage of 95 55% and 96.12%. The N-gain test yielded medium and high criteria for efficacy. The research's findings indicate that problem solving focused student worksheets are a workable way to support students in strengthening their capacity for critical thought when studying acid-base content.